2013
DOI: 10.4300/jgme-d-12-00214.1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of a Structured Curriculum in Teaching Procedural and Basic Diagnostic Ultrasound Skills to Internal Medicine Residents

Abstract: Background Point-of-care ultrasound has emerged as a powerful diagnostic tool and is also being increasingly used by clinicians to guide procedures. Many current and future internists desire training, yet no formal, multiple-application, program-wide teaching interventions have been described. Intervention We describe a structured 30-hour ultrasound training course in diagnostic and procedural ultrasound implemented during in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…Similarly, the Society of Hospital Medicine is actively releasing position statements on certification in point‐of‐care ultrasonography and creating a certification program (https://www.hospitalmedicine.org/clinical-topics/ultrasonography-cert/). In response, some internal medicine residency programs have identified the need to train their residents and hence have preemptively developed formal curricula in point‐of‐care ultrasonography . How best to instruct and how often to retrain noncardiologists in FCU remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the Society of Hospital Medicine is actively releasing position statements on certification in point‐of‐care ultrasonography and creating a certification program (https://www.hospitalmedicine.org/clinical-topics/ultrasonography-cert/). In response, some internal medicine residency programs have identified the need to train their residents and hence have preemptively developed formal curricula in point‐of‐care ultrasonography . How best to instruct and how often to retrain noncardiologists in FCU remains unclear.…”
mentioning
confidence: 99%
“…In response, some internal medicine residency programs have identified the need to train their residents and hence have preemptively developed formal curricula in point-of-care ultrasonography. [3][4][5][6] How best to instruct and how often to retrain noncardiologists in FCU remains unclear.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of the excluded papers, five had heterogeneous study groups which included or focused on more senior clinicians, three did not objectively assess the study group post-intervention, and two did not have a practical image acquisition component to the assessments. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of the excluded papers, five had heterogeneous study groups which included or focused on more senior clinicians, three did not objectively assess the study group post-intervention, and two did not have a practical image acquisition component to the assessments.…”
Section: Resultsmentioning
confidence: 99%
“…The 25 articles were read in full and ten were excluded with 15 papers in total included in the review. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of the excluded papers, five had heterogeneous study groups which included or focused on more senior clinicians, three did not objectively assess the study group post-intervention, and two did not have a practical image acquisition component to the assessments. A study flowchart is provided in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…1 While other studies have shown the feasibility of implementing point-of-care ultrasound curricula for internal medicine residents, the trial by Ojeda et al had disappointing results. 2 Several key factors were likely contributory. One major limitation of this trial was that only 1.5 h of didactic and 1.5 h of hands-on training were used in the intervention group.…”
Section: T O the Editorsmentioning
confidence: 99%